2003
DOI: 10.1046/j.1365-2443.2003.00655.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel rabconnectin‐3‐binding protein that directly binds a GDP/GTP exchange protein for Rab3A small G protein implicated in Ca2+‐dependent exocytosis of neurotransmitter

Abstract: Background : Rab3A, a member of the Rab3 small G protein family, regulates Ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 23 publications
0
61
0
Order By: Relevance
“…Again, the Rab3A-regulated hub of the synapse provides the best validation of the approach. We observe tight coclustering of Rab3A with three distinct groups: 1) Rab regulators and effectors including GDI1(␣) (Sudhof, 2004), RIM3, Rabphilin-3A (Fukuda, 2003), calmodulin (Park et al, 1997), Synapsin (Syn1; Giovedi et al, 2004aGiovedi et al, , 2004b, Rab3 GEP-binding protein Rabconnectin-3 beta (Kawabe et al, 2003), and a potential RabGAP, RUTBC1 (Katoh, 2004); 2) SNARE system components including VAMP2, NSF (Chen and Scheller, 2001;Gerst, 2003;Sollner, 2003;Ungar and Hughson, 2003), Synaptotagmin I (Koh and Bellen, 2003), and Synaptophysin (Calakos and Scheller, 1994); and finally 3) coat machinery components AP3 2 (Hinners and Tooze, 2003), DNJC6/Auxilin, and Dynamin III (Lafer, 2002). Although Dynamin I has a broad tissue distribution and has a distinct clustering profile, the striking linkage of Dynamin III to Rab3A suggests a central, if not specialized, role in the synapse (Gray et al, 2003).…”
Section: The Membromementioning
confidence: 79%
See 1 more Smart Citation
“…Again, the Rab3A-regulated hub of the synapse provides the best validation of the approach. We observe tight coclustering of Rab3A with three distinct groups: 1) Rab regulators and effectors including GDI1(␣) (Sudhof, 2004), RIM3, Rabphilin-3A (Fukuda, 2003), calmodulin (Park et al, 1997), Synapsin (Syn1; Giovedi et al, 2004aGiovedi et al, , 2004b, Rab3 GEP-binding protein Rabconnectin-3 beta (Kawabe et al, 2003), and a potential RabGAP, RUTBC1 (Katoh, 2004); 2) SNARE system components including VAMP2, NSF (Chen and Scheller, 2001;Gerst, 2003;Sollner, 2003;Ungar and Hughson, 2003), Synaptotagmin I (Koh and Bellen, 2003), and Synaptophysin (Calakos and Scheller, 1994); and finally 3) coat machinery components AP3 2 (Hinners and Tooze, 2003), DNJC6/Auxilin, and Dynamin III (Lafer, 2002). Although Dynamin I has a broad tissue distribution and has a distinct clustering profile, the striking linkage of Dynamin III to Rab3A suggests a central, if not specialized, role in the synapse (Gray et al, 2003).…”
Section: The Membromementioning
confidence: 79%
“…For example, Rab3A clusters with HERC1 (Rosa et al, 1996) and the potential GEF Syn1 (Giovedi et al, 2004a). Although the Rab3A GEF Rab3GEP and GAP Rab3GAP have more divergent distributions suggestive of interaction with other Rab GTPases, the Rab3A-hub did contain the Rab3GEP-interacting protein Rabconnectin-3 beta (Kawabe et al, 2003), which may provide added specificity to Rab3A GEF recognition in vivo. As a second example, clustering of ALS2 (Otomo et al, 2003) with Rab5A; syntenin (Tomoda et al, 2004) with Rab5C; and RASA1, APPL1, and APPL2 (Miaczynska et al, 2004) with Rab5B ( Figure 2) is also in good agreement with well-established biochemical data and highlights potential strong differences in isoform activity in different tissues.…”
Section: Rab Regulators Rab Gtpases Do Not Function In Isolationmentioning
confidence: 99%
“…Therefore, it is likely that the mutated protein of p130 lacking Rab3 GAP activity is expressed in the patients, whereas p130 is not expressed in our mice. This mutated protein could interact with various proteins, such as the noncatalytic subunit p150 (15), rabconnectin-3 (31,32), and the unidentified proteins as well as the intact protein. Another possibility is that this mutated p130 may suppress (or stimulate) the functions of these interacting proteins, resulting in the generation of abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…One such class of mutants are those affecting the Rabconnectin-3 complex, a heterodimer of the proteins Rabconnectin-3α and Rabconnectin-3β (Rbcn-3A and Rbcn-3B in Drosophila) (Kawabe et al, 2003;Nagano et al, 2002). Preliminary data indicated that loss of Rbcn-3A in terminal cells leads to defects in terminal cell lumen formation (M.M.M.…”
Section: Identification Of Candidate Luminal Intermediates In Developmentioning
confidence: 99%